2019
DOI: 10.1016/j.jneuroim.2018.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Effects of inflammatory cytokines IFN-γ, TNF-α and IL-6 on the viability and functionality of human pluripotent stem cell-derived neural cells

Abstract: Multiple Sclerosis (MS) is an inflammatory neurodegenerative disease, where neural progenitor cell (NPC) transplantation has been suggested as a potential neuroprotective therapeutic strategy. Since the effect of inflammation on NPCs is poorly known, their effect on the survival and functionality of human NPCs were studied. Treatment with interleukin (IL)-6, tumor necrosis factor (TNF)-α and interferon (IFN)-γ did not induced cytotoxicity, but IFN-γ treatment showed decreased proliferation and neuronal migrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“… 6 IFN-γ, TNF-α, and IL-6 also reportedly modulate proliferation as well as both cellular and functional properties of human neural pluripotent cells in vitro. 7 In this study, IL-6 was expressed only in SHED, and IL-3 was 2.77-fold more strongly detected in SHED. Of the core cytokines, SCF and Flt3-L were expressed more strongly in DPSCs and SHED, respectively.…”
Section: Discussionmentioning
confidence: 45%
“… 6 IFN-γ, TNF-α, and IL-6 also reportedly modulate proliferation as well as both cellular and functional properties of human neural pluripotent cells in vitro. 7 In this study, IL-6 was expressed only in SHED, and IL-3 was 2.77-fold more strongly detected in SHED. Of the core cytokines, SCF and Flt3-L were expressed more strongly in DPSCs and SHED, respectively.…”
Section: Discussionmentioning
confidence: 45%
“…Of note, one EAE study showed that chitinase 3-like-3 (Chi3l3) activates the epidermal growth factor receptor (EGFR) on neural stem cells, which results in decreased disease severity [81]. Moreover, chemokines are important for stem cell proliferation, resulting in a lower capacity to differentiate into oligodendrocytes, and an increased differentiation into neuronal progenitors [77,82]. In contrast, transplanted NSCs were shown to participate directly in the remyelination of damaged axons [83], but also to influence OPC-based myelin regeneration after cuprizone-mediated demyelination [84].…”
Section: Neural Stem Cells (Nscs)mentioning
confidence: 99%
“…Advancements in the field of stem cell biology have enabled the differentiation of astrocytes from human pluripotent stem cells (hPSCs) 1822 , providing an unlimited cell source and an option to create disease-specific cell lines. Despite these advancements, only a few studies have described the reactivation of hPSC-derived astrocytes 18,2225 , and even fewer studies have reported the interplay of inflammation or reactive astrocytes with human neuronal cells 24,26,27 .…”
Section: Introductionmentioning
confidence: 99%